A foldable yoga mat for nap and preparation method thereof

By adding bamboo fibers and thermally expanded microspheres to the polyurethane elastic layer of the yoga mat and carrying out specific preparation and processing, the problem of insufficient sound insulation performance of the existing yoga mat is solved, better noise isolation effect is achieved, and users are improved Quality of rest.

CN117986518BActive Publication Date: 2025-02-11SANSD JIANGSU ENVIRONMENTAL PROTECTION TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410126178.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-01-30
Publication Date
2025-02-11
Estimated Expiration
2044-01-30

AI Technical Summary

Technical Problem

The sound insulation performance of existing polyurethane yoga mats is limited, making it difficult to effectively block the noise emitted by users and the noise emitted by the ground, affecting the quality of rest of the user.

Method used

By optimizing the A-material formula, adding bamboo fibers and thermally expanded microspheres, and baking and cooling treatments are carried out during the preparation of the polyurethane elastic layer, the foaming effect and sonic absorption capacity of the polyurethane layer are enhanced.

Benefits of technology

It significantly improves the sound insulation performance of the yoga mat, can effectively block the noise emitted by users and the noise emitted by the ground, and improves the quality of rest for users.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004688325840000061
    Figure BDA0004688325840000061
  • Figure BDA0004688325840000062
    Figure BDA0004688325840000062
  • Figure BDA0004688325840000071
    Figure BDA0004688325840000071
Patent Text Reader

Abstract

The present application relates to the technical field of yoga mat preparation, and specifically discloses a folding yoga mat for napping and a preparation method thereof. The yoga mat includes fabric and a polyurethane elastic layer, and the polyurethane elastic layer is made by mixing A material and B material in a weight ratio of (1.8-1.84): 1; A material includes the following components in parts by weight: 90-98 parts of polyether polyols, 0.5-0.7 parts of antioxidants, 2-2.4 parts of deionized water, 0.4-0.6 parts of surfactants, 0.6-0.8 parts of catalysts, 4-10 parts of filling fibers, and 1.8-2.4 parts of thermal expansion microspheres; Filling fibers include bamboo fiber, and the components of B material include diisocyanate and pore-opening agent. The yoga mat of the present application can not only effectively block the noise emitted by the user when actually used, but also when the user lies on the yoga mat for rest, the yoga mat can also effectively isolate the noise from the ground, which is conducive to improving the rest quality of the user.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of yoga mat preparation, and more specifically, to a nap folding yoga mat and a preparation method thereof. Background Art

[0002] A yoga mat is a soft cushion with certain protective functions. When doing indoor sports such as yoga and rope skipping, laying a yoga mat can reduce the risk of practitioners falling and getting injured, and can also block the cold air on the ground. In addition to being used during practice, yoga mats can also be used for practitioners to lie down and rest during breaks. Based on this use, yoga mats can also be used as carpets in daily homes. At present, most yoga mats on the market are made of elastic materials and fabrics, and have a certain degree of foldability. Considering that yoga mats need to be in contact with the human body for a long time, the elastic material used to prepare yoga mats should not have too obvious odor, and it is best to be able to be formed in one go. For the above reasons, polyurethane foam materials are often used in the production of yoga mats.

[0003] In the related art, there is a yoga mat, which includes a fabric and a polyurethane elastic layer adhered to one side of the fabric. The polyurethane elastic layer is obtained by mixing material A and material B in a weight ratio of 1.8:1, reacting at 50°C for 6 minutes, and then cutting. Material A includes the following raw materials by weight: 90 parts of polyether polyol, 0.5 parts of anti-aging additives, 0.4 parts of foam regulators, 2 parts of deionized water, 0.4 parts of silicone surfactants, 0.6 parts of composite catalysts and 0.5 parts of polyhexamethylene guanidine hydrochloride; the viscosity of the polyether polyol is 3000mPa.s, the hydroxyl value is 48mgKOH / g, and the functionality is 2. Material B is composed of diisocyanate and a pore opener with a weight of 4% of diisocyanate, the diisocyanate is toluene diisocyanate, and the pore opener is N-hydroxyethyl-cyanoacetamide.

[0004] With regard to the above-mentioned related technologies, the inventor believes that the polyurethane yoga mats in the related technologies have limited sound insulation performance. When the user's movements are more intense, it is difficult to completely block the noise made by the user, which is easy to cause inconvenience to others. When the user lies on the yoga mat to rest, the yoga mat is also difficult to fully isolate the noise from the ground, which is not conducive to improving the user's rest quality. Summary of the invention

[0005] The polyurethane yoga mat in the related art has limited sound insulation performance. Not only is it difficult for the yoga mat to fully block the noise emitted by the user, but also when the user lies on the yoga mat to rest, the yoga mat is difficult to fully isolate the noise from the ground, which is not conducive to improving the rest quality of the user. In order to improve this defect, the present application provides a nap folding yoga mat and a preparation method thereof.

[0006] In the first aspect, the present application provides a foldable yoga mat for napping, which adopts the following technical solution:

[0007] A foldable yoga mat for naps, comprising a fabric and a polyurethane elastic layer, wherein the polyurethane elastic layer is prepared by mixing a material A and a material B in a weight ratio of (1.8-1.84):1; the material A comprises the following components in parts by weight: 90-98 parts of polyether polyol, 0.5-0.7 parts of an antioxidant, 2-2.4 parts of deionized water, 0.4-0.6 parts of a surfactant, 0.6-0.8 parts of a catalyst, 4-10 parts of filling fibers, and 1.8-2.4 parts of thermal expansion microspheres; the filling fibers comprise bamboo fibers, and the components of the material B comprise diisocyanate and a pore-opening agent.

[0008] By adopting the above technical scheme, the present application optimizes the formula of material A in the related art, and adds filling fiber and heat-expandable microspheres to material A, and at the same time limits the filling fiber to include bamboo fiber. In the process of mixing reaction of material A and material B, a part of the hydroxyl groups on the surface of bamboo fiber can react with the isocyanate groups in material B and realize the combination with polyurethane. After baking and cooling, the heat-expandable microspheres can produce closed pores in polyurethane, which improves the foaming effect of polyurethane elastic layer on the basis of the original foaming system. The bamboo fiber combined with polyurethane can produce synergistic effect with the pores in the polyurethane elastic layer, and has a certain absorption and blocking effect on the sound waves when the sound waves pass through the polyurethane elastic layer. Therefore, the polyurethane elastic layer prepared by the formula of the present application and baked can give the yoga mat good sound insulation performance. The yoga mat of the present application can not only effectively block the noise emitted by the user when it is actually used, but also when the user lies on the yoga mat to rest, the yoga mat can effectively isolate the noise from the ground, which is conducive to improving the rest quality of the user.

[0009] Preferably, the bamboo fiber is pretreated before use according to the following method:

[0010] Prepare a sodium hydroxide solution with a mass fraction of 8-22% and set it aside; add the bamboo fiber into the sodium hydroxide solution and soak it for 60-120 minutes, then take out the bamboo fiber and dry it, so as to complete the pretreatment of the bamboo fiber.

[0011] By adopting the above-mentioned technical scheme, the present application uses sodium hydroxide solution to pretreat the bamboo fibers. The sodium hydroxide solution can remove the fiber colloid on the surface of the bamboo fibers and fully free the hydroxyl groups in the cellulose clean area on the surface of the bamboo fibers, thereby promoting the full reaction of the bamboo fibers and diisocyanate, enhancing the bonding effect of the bamboo fibers and polyurethane, and helping to improve the sound insulation performance of the yoga mat.

[0012] Preferably, in the method for pretreating the bamboo fibers, the mass fraction of sodium hydroxide in the sodium hydroxide solution is 15-22%.

[0013] By adopting the above technical scheme, the present application optimizes the mass fraction of sodium hydroxide in the sodium hydroxide solution, improves the pretreatment effect on bamboo fibers, enhances the bonding effect between bamboo fibers and polyurethane, and helps to improve the sound insulation performance of the yoga mat.

[0014] Preferably, in the method for pretreating the bamboo fibers, the bamboo fibers are immersed in the sodium hydroxide solution for 100-120 minutes.

[0015] By adopting the above technical scheme, the present application optimizes the treatment time of the bamboo fiber with the sodium hydroxide solution, improves the pretreatment effect on the bamboo fiber, enhances the bonding effect between the bamboo fiber and the polyurethane, and helps to improve the sound insulation performance of the yoga mat.

[0016] Preferably, in the method for pretreating the bamboo fibers, the mass fraction of sodium hydroxide in the sodium hydroxide solution is 22%, and the bamboo fibers are immersed in the sodium hydroxide solution for 120 minutes.

[0017] By adopting the above technical scheme, the present application optimizes the mass fraction of sodium hydroxide and the treatment time of the sodium hydroxide solution on the bamboo fiber, improves the pretreatment effect on the bamboo fiber, enhances the bonding effect between the bamboo fiber and the polyurethane, and helps to improve the sound insulation performance of the yoga mat.

[0018] Preferably, the filling fiber is formed by mixing bamboo fiber and modified bamboo fiber in a weight ratio of (1-5):1, and the modified bamboo fiber is prepared according to the following method:

[0019] (1) mixing tetraethyl orthosilicate, hydroxymethyltriethoxysilane, deionized water and anhydrous ethanol in a molar ratio of 1:(0.6-1):(8-10):(30-34) to obtain a silane-modified liquid for later use;

[0020] (2) adding the pretreated bamboo fibers and nano-mica powder to a silane-modified solution to obtain a mixed solution, adjusting the pH of the mixed solution to 3-4, and ultrasonically dispersing the mixed solution in a constant temperature water bath at 45-50° C. for 90-120 min. After standing for 3-4 h, taking out the fibers from the mixed solution and drying them to obtain modified bamboo fibers. In this step, the pretreated bamboo fibers are added to the silane-modified solution at a ratio of 1 kg: (4-8) L, and the amount of the nano-mica powder is 5-17% of the weight of the pretreated bamboo fibers.

[0021] By adopting the above technical scheme, the present application modifies the pretreated bamboo fiber by silane modification liquid, and the tetraethyl orthosilicate can condense with the hydroxyl group on the surface of the bamboo fiber, and further condense on the surface of the bamboo fiber to form silicon dioxide. While silicon dioxide is formed, the tetraethyl orthosilicate can also condense with the nano mica powder, and the nano mica powder is loaded on the surface of the bamboo fiber. After the condensation of hydroxymethyl triethoxy silane and tetraethyl orthosilicate, hydroxyl groups can be introduced on the surface of silicon dioxide, so that the modified bamboo fiber can be combined with diisocyanate by reaction. The introduction of nano mica powder can improve the sound insulation effect, and since the nano mica powder is silicon dioxide produced by the condensation of tetraethyl orthosilicate, it can be loaded on the surface of the bamboo fiber, and this loading process is realized under ultrasonic dispersion conditions, thus overcoming the defect that the nano mica powder is easy to agglomerate. When the filling fiber includes the above modified bamboo fiber, the dispersion effect of the filling fiber is better, which can overcome the defect that the bamboo fiber content is easy to agglomerate when it is high, and help to fully improve the sound insulation performance of the yoga mat.

[0022] Preferably, in step (2) of preparing the modified bamboo fiber, the pretreated bamboo fiber is added to the silane modification liquid at a ratio of 1 kg: (6-8) L.

[0023] By adopting the above technical solution, the present application optimizes the usage ratio of bamboo fiber and silane modified liquid, which helps to fully improve the sound insulation performance of the yoga mat.

[0024] Preferably, in the step (2) of preparing the modified bamboo fiber, the amount of nano-mica powder used is 12-17% of the weight of the pretreated bamboo fiber.

[0025] By adopting the above technical solution, the present application optimizes the dosage of nano-mica powder, which helps to fully improve the sound insulation performance of the yoga mat.

[0026] Preferably, the filling fiber is formed by mixing bamboo fiber and modified bamboo fiber in a weight ratio of (1-3):1.

[0027] By adopting the above technical solution, the present application optimizes the usage ratio of bamboo fiber and modified bamboo fiber. According to the above preferred usage ratio, the defect of easy agglomeration of filling fibers can be fully overcome, thereby improving the sound insulation performance of the yoga mat.

[0028] In a second aspect, the present application provides a method for preparing a foldable yoga mat for napping, adopting the following technical solution.

[0029] A method for preparing a foldable yoga mat for napping, comprising the following steps:

[0030] (1) Mixing polyether polyol, antioxidant, deionized water, surfactant, catalyst, filling fiber, and heat-expandable microspheres to obtain material A; mixing diisocyanate and a cell-opening agent to obtain material B; laying the fabric in a mold for later use;

[0031] (2) Mix material A and material B, inject the obtained mixture into a mold, react at 40-50° C. for 5-6 minutes, then pre-bake the obtained product at 80-90° C. for 50-60 seconds, and then bake at 170-180° C. for 40-60 seconds, and then cool, demold and cut to obtain a nap folding yoga mat.

[0032] By adopting the above technical scheme, the present application mixes material A and material B in a mold and then processes them, and then pre-bakes and bakes them in sequence to expand the heat-expandable microspheres, and then cools them to complete the foaming of the heat-expandable microspheres, thereby obtaining a nap folding yoga mat with good sound insulation performance.

[0033] In summary, this application has the following beneficial effects:

[0034] 1. The yoga mat of the present application can not only effectively block the noise made by the user during actual use, but also effectively isolate the noise from the ground when the user lies on the yoga mat to rest, which is beneficial to improving the rest quality of the user.

[0035] 2. Apply to modify the pre-treated bamboo fibers with silane modification liquid, load silica and nano-mica powder on the surface of the bamboo fibers, and introduce hydroxyl groups through hydroxymethyltriethoxysilane, which can overcome the defect of easy agglomeration of bamboo fibers when the content is high, and help to fully improve the sound insulation performance of yoga mats.

[0036] 3. The method of the present application is to first mix material A and material B in a mold and then process them, and then pre-bake and bake them in sequence to expand the heat-expandable microspheres, and then cool them to complete the foaming of the heat-expandable microspheres, so as to obtain a nap folding yoga mat with good sound insulation performance. DETAILED DESCRIPTION

[0037] The present application is further described in detail below in conjunction with embodiments, preparation examples and comparative examples. The raw materials involved in the present application can all be obtained commercially.

[0038] Preparation example of bamboo fiber

[0039] The following is an explanation using Preparation Example 1.

[0040] Preparation Example 1

[0041] In this preparation example, bamboo fiber was pretreated according to the following method:

[0042] Prepare a sodium hydroxide solution with a mass fraction of 8% and set it aside; add bamboo fibers with an average linear density of 12.6 dtex and an average length of 65 mm into the sodium hydroxide solution and soak for 60 minutes, then fish out the bamboo fibers and dry them, thereby completing the pretreatment of the bamboo fibers.

[0043] As shown in Table 1, the difference between Preparation Examples 1-5 is that the sodium hydroxide concentration in the sodium hydroxide solution is different.

[0044] Table 1 Sodium hydroxide concentration

[0045] sample Sodium hydroxide concentration / (mol / L) Preparation Example 1 8 Preparation Example 2 11 Preparation Example 3 15 Preparation Example 4 18 Preparation Example 5 22

[0046] As shown in Table 2, the difference between Preparation Examples 5-9 is that the bamboo fibers are immersed in the sodium hydroxide solution for different times.

[0047] Table 2 Soaking time

[0048] sample Soaking time / min Preparation Example 5 60 Preparation Example 6 80 Preparation Example 7 100 Preparation Example 8 110 Preparation Example 9 120

[0049] Preparation example of modified bamboo fiber

[0050] The following is an explanation using Preparation Example 10 as an example.

[0051] Preparation Example 10

[0052] In this preparation example, the modified bamboo fiber was prepared according to the following method:

[0053] (1) mixing tetraethyl orthosilicate, hydroxymethyltriethoxysilane, deionized water and anhydrous ethanol in a molar ratio of 1:0.6:8:30 (hereinafter referred to as the silane-modified liquid ratio) to obtain a silane-modified liquid for standby use;

[0054] (2) The bamboo fibers pretreated according to the method of Preparation Example 9 were added to the silane-modified liquid at a ratio of 1 kg:4 L, and nano-mica powder with an average particle size of 86 nm was added to the silane-modified liquid in an amount equivalent to 5% of the weight of the pretreated bamboo fibers to obtain a mixed solution, the pH of the mixed solution was adjusted to 4 with hydrochloric acid, and ultrasonically dispersed for 90 min (i.e., the modification time in Table 3) under a constant temperature water bath condition of 45° C. (i.e., the water bath temperature in Table 3), and after standing for 3 h (i.e., the standing time in Table 3), the fibers in the mixed solution were taken out and dried to obtain modified bamboo fibers.

[0055] As shown in Table 3, the differences between Preparation Examples 10-14 are that the ratio of silane modification solution, pH value of the mixed solution, water bath temperature, modification time and standing time are different.

[0056] Table 3 Silane modification liquid ratio, mixed liquid pH, water bath temperature, modification time and standing time

[0057]

[0058] As shown in Table 4, the difference between Preparation Examples 14-18 is that the usage ratio of the pretreated bamboo fiber and the silane modification liquid is different.

[0059] Table 4 The usage ratio of bamboo fiber and silane modified liquid

[0060] sample Bamboo fiber (kg): Silane modified liquid (L) Preparation Example 14 1:4 Preparation Example 15 1:5 Preparation Example 16 1:6 Preparation Example 17 1:7 Preparation Example 18 1:8

[0061] As shown in Table 5, the difference between Preparation Examples 18-22 is that the percentage of the amount of nano mica powder used in the weight of the pretreated bamboo fiber (hereinafter referred to as mica powder percentage) is different.

[0062] Table 5 Mica powder proportion

[0063]

[0064]

[0065] Example

[0066] Examples 1-5

[0067] The following description is given by taking Example 1 as an example.

[0068] Example 1

[0069] This embodiment provides a foldable yoga mat for napping, comprising a fabric and a polyurethane elastic layer, wherein the polyurethane elastic layer is made by mixing material A and material B at a weight ratio of 1.8:1.

[0070] Material A includes the following components: 90kg of polyether polyol, 0.5kg of antioxidant, 2kg of deionized water, 0.4kg of surfactant, 0.6kg of catalyst, 4kg of filling fiber, and 1.8kg of heat-expandable microspheres; the filling fiber is bamboo fiber with an average linear density of 12.6dtex and an average length of 65mm, the heat-expandable microspheres are 180DU45 heat-expandable plastic foamed microspheres, the antioxidant is 3-(3,5-di-tert-butyl-4-hydroxyphenyl) methyl propionate, the surfactant is L6912 silicone surfactant, the catalyst is compounded by an amine catalyst and an organotin catalyst in a weight ratio of 2:1, the amine catalyst is diethylenetriamine, and the organotin catalyst is dibutyltin dilaurate; the viscosity of the polyether polyol is 3000mPa.s, the hydroxyl value is 48mgKOH / g, and the functionality is 2.

[0071] Material B is composed of diisocyanate and a pore opening agent with a weight percentage of 4% of the diisocyanate. The diisocyanate is toluene diisocyanate and the pore opening agent is N-hydroxyethyl-cyanoacetamide.

[0072] In this embodiment, the nap folding yoga mat is prepared according to the following steps:

[0073] (1) Mix polyether polyol, antioxidant, deionized water, surfactant, catalyst, filling fiber, and heat-expandable microspheres to obtain material A; mix diisocyanate and pore-opening agent to obtain material B; lay the fabric in a mold for later use; the fabric has a thickness of 0.6 mm and a density of 1.4 g / cm 3 PU artificial leather;

[0074] (2) Material A and material B are mixed, and the obtained mixture is injected into a mold, and the mold pressure is set to 0.5 MPa. The mixture is reacted at 40°C (i.e., the reaction temperature in Table 5) for 5 min (i.e., the reaction time in Table 5), and then the obtained product is pre-baked at 80°C (i.e., the pre-baking temperature in Table 5) for 50 s (i.e., the pre-baking time in Table 5), and then baked at 170°C (i.e., the baking temperature in Table 5) for 40 s (i.e., the baking time in Table 5), and then cooled, demolded and cut to obtain a nap folding yoga mat with a thickness of 6.5 mm.

[0075] As shown in Table 6, the differences between Examples 1-5 mainly lie in the ratio of material A to material B, the raw material ratio of material A, and some processing parameters.

[0076] Table 6 Ratio of material A to material B, raw material ratio of material A and some processing parameters

[0077]

[0078]

[0079] Example 6

[0080] The difference between this embodiment and embodiment 5 is that the bamboo fiber of preparation example 1 is selected as the filling fiber.

[0081] As shown in Table 7, the difference between Examples 6-14 is that the preparation examples of bamboo fibers are different.

[0082] Table 7 Preparation example of bamboo fiber

[0083] sample Preparation Example sample Preparation Example Example 6 Preparation Example 1 Embodiment 11 Preparation Example 6 Example 7 Preparation Example 2 Example 12 Preparation Example 7 Example 8 Preparation Example 3 Embodiment 13 Preparation Example 8 Example 9 Preparation Example 4 Embodiment 14 Preparation Example 9 Example 10 Preparation Example 5 / /

[0084] Embodiment 15

[0085] The difference between this embodiment and embodiment 14 is that the filling fiber is formed by mixing bamboo fiber and modified bamboo fiber in a weight ratio of 5:1, and the modified bamboo fiber is prepared according to the method of preparation example 10.

[0086] As shown in Table 8, the difference between Examples 15-27 is that the preparation examples of the modified bamboo fiber are different.

[0087] Table 8 Preparation example of modified bamboo fiber

[0088] sample Preparation Example sample Preparation Example Embodiment 15 Preparation Example 10 Embodiment 22 Preparation Example 17 Example 16 Preparation Example 11 Embodiment 23 Preparation Example 18 Embodiment 17 Preparation Example 12 Embodiment 24 Preparation Example 19 Embodiment 18 Preparation Example 13 Embodiment 25 Preparation Example 20 Embodiment 19 Preparation Example 14 Embodiment 26 Preparation Example 21 Embodiment 20 Preparation Example 15 Embodiment 27 Preparation Example 22 Embodiment 21 Preparation Example 16 / /

[0089] As shown in Table 9, the difference between Examples 27-31 is that the filling fiber is a mixture of bamboo fiber and modified bamboo fiber in different weight ratios.

[0090] Table 9 Filling fiber ratio

[0091] sample Bamboo fiber: modified bamboo fiber Embodiment 27 5:1 Embodiment 28 4:1 Embodiment 29 3:1 Embodiment 30 2:1 Embodiment 31 1:1

[0092] Comparative Example

[0093] Comparative Example 1

[0094] This comparative example provides a polyurethane yoga mat, including a fabric and a polyurethane elastic layer adhered to one side of the fabric, with a total thickness of 6.5 mm, a fabric thickness of 0.6 mm, and a density of 1.4 g / cm 3 PU artificial leather.

[0095] The polyurethane elastic layer is obtained by mixing material A and material B at a weight ratio of 1.8:1, reacting at 50°C for 6 minutes, and then cutting. Material A includes the following raw materials: 90kg polyether polyol, 0.5kg anti-aging additive, 0.4kg foam regulator, 2kg deionized water, 0.4kg silicone surfactant, 0.6kg compound catalyst and 0.5kg polyhexamethylene guanidine hydrochloride; the viscosity of the polyether polyol is 3000mPa.s, the hydroxyl value is 48mgKOH / g, and the functionality is 2; the surfactant is L6912 silicone surfactant; the compound catalyst is compounded by an amine catalyst and an organotin catalyst at a weight ratio of 2:1, the amine catalyst is diethylenetriamine; the organotin catalyst is dibutyltin dilaurate. Material B is composed of diisocyanate and a pore opener with a weight of 4% of diisocyanate, the diisocyanate is toluene diisocyanate, and the pore opener is N-hydroxyethyl-cyanoacetamide.

[0096] The foam control agent of this comparative example is prepared according to the following method:

[0097] (1) Preparation of inorganic substrate: Nano-silica microspheres with an average particle size of 2 μm and dopamine were added to the same portion of deionized water at a solid-liquid ratio of 0.05 g / mL and 0.02 g / mL, respectively. The temperature of the resulting mixed solution was adjusted to 20° C. and ultrasonically dispersed at this temperature for 10 min. After sealed and stirred for 3 h, ammonium persulfate with a mass ratio of 25% of dopamine was added to the mixed solution. After stirring for 20 h, the resulting mixture was centrifuged and freeze-dried in sequence, and the resulting solid micropowder was stored for later use. The resulting solid micropowder was placed in a nitrogen atmosphere and kept at 320° C. for 50 min, and then kept at 650° C. for 70 min. After naturally cooling to room temperature, the finished inorganic substrate was obtained.

[0098] (2) Pretreatment of inorganic substrate: The inorganic substrate obtained above was added into a mixed acid solution prepared by mixing concentrated sulfuric acid (85%) and concentrated nitric acid (68%) in a volume ratio of 3:1 at a dosage ratio of 0.02 g / mL, and ultrasonically reacted in a water bath at 60°C for 2 h. After the reaction was completed, it was naturally cooled to room temperature (20°C); then diluted with deionized water whose volume was 8 times that of the mixed acid solution, and allowed to stand at room temperature for 20 h, the upper layer solution was poured off, and the remaining bottom layer material was filtered and rinsed; until the pH was neutral, and then the obtained solid component was vacuum dried to complete the pretreatment of the inorganic substrate;

[0099] (3) Formal preparation: The inorganic substrate after pretreatment is immersed in an impregnation liquid with a mass of 8 times that of the inorganic substrate and a temperature of 40°C. After ultrasonic dispersion for 10 minutes, γ-methacryloxypropyltrimethoxysilane with a volume of 20% of the impregnation liquid is added to the impregnation liquid, and the pH is adjusted to 4 with acetic acid. After the hydrolysis of γ-methacryloxypropyltrimethoxysilane is completed, it is stirred and dispersed evenly, and the reaction is stirred and reacted at 60°C for 2 hours; after the reaction is completed, the obtained reaction product is filtered, washed and dried in turn, and the obtained solid particles are the finished foam control agent. The preparation method of the impregnation liquid is: add 5% of the mass of dodecyltrimethylammonium chloride to a 50% ethanol aqueous solution, and after uniform dispersion, the finished impregnation liquid is obtained.

[0100] The anti-aging additive selected in this comparative example was prepared according to the following method:

[0101] (1) Modification of porous nanopowders: Porous nanopowders with an average particle size of 90 nm were added to an ethanol mixture at a solid-liquid ratio of 0.08 g / mL. Under ultrasonic dispersion, 3-aminopropyltrimethoxysilane was added to the ethanol mixture at a mass of 20% of the porous nanopowder. The pH of the resulting mixed solution was adjusted to 2.5 with glacial acetic acid, and the mixture was stirred and reacted at 40°C for 2 h. After the reaction was completed, the resulting mixed reaction product was filtered, washed twice with ethanol, and finally dried at 50°C to complete the modification of the porous nanopowders.

[0102] (2) Formal preparation: methyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate is added to a mixed solvent at a solid-liquid ratio of 0.08 g / mL, and then a porous nanopowder and a reaction accelerator with a mass of 20% of methyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate are added to the obtained mixed liquid phase respectively. After ultrasonic dispersion for 10 minutes, the mixture is stirred and reacted at 90°C in an inert gas atmosphere for 8 hours. After the reaction is completed, the obtained product components are filtered, washed and dried in turn, and the obtained solid powder is the finished anti-aging additive. The mixed solvent is prepared by mixing toluene and ethylene glycol in a volume ratio of 8:1. The reaction accelerator is dibutyltin oxide, and the amount used is 2.5% of the porous nanopowder.

[0103] The preparation method of porous nanopowder is:

[0104] Titanyl sulfate is added to distilled water to obtain a titanium-containing solution with a titanyl sulfate concentration of 0.2 mol / L, and ethanol with a volume 0.5 times that of the titanium-containing solution is added to the titanium-containing solution. After mechanical stirring and mixing, the obtained mixed solution is sealed and placed in a reactor, and kept warm for reaction at a temperature of 130°C for 15 hours. After the reaction is completed, a sodium hydroxide solution with a concentration of 0.005 mol / L is used to remove and separate the product components obtained in the reactor, and then the product is washed and dried in sequence to obtain a porous nanopowder product with an average particle size of 90 nm.

[0105] The preparation method of the ethanol mixed liquid is as follows: 12% by weight of didecyldimethylammonium chloride and 2.5% by weight of fatty alcohol polyoxyethylene ether are added to a 60% ethanol aqueous solution, and the mixture is uniformly dispersed by ultrasonic to obtain the ethanol mixed liquid.

[0106] The preparation method of a polyurethane yoga mat comprises the following steps:

[0107] (1) Weighing each raw material according to the above formula, and then uniformly mixing the polyether polyol, anti-aging additive, foam control agent, deionized water, silicone surfactant and composite catalyst to obtain component A; sending component A to the A material storage tank of the high-pressure foaming machine for storage;

[0108] (2) After the modified isocyanate and the cell opening agent are uniformly mixed, component B is obtained; and then component B is sent to the B material storage tank of the high-pressure foaming machine for storage and standby; wherein the pressure value of the A material storage tank of the high-pressure foaming machine and the B material storage tank of the high-pressure foaming machine is 0.25 MPa;

[0109] (3) Set the high-pressure foaming machine according to the weight ratio of component A to component B of 1.8:1, adjust the mold (mold frame) pressure to 0.5 MPa, set the mold temperature to 50°C, and then lay the fabric or leather flat under the mold;

[0110] (4) Using a high-pressure foaming machine injection head, inject the mixture obtained by mixing component A and component B into the mold; closing the mold to allow the material liquid to undergo chemical reaction in the mold, and the reaction time is set to 5 minutes;

[0111] (5) After the reaction is completed, the mold is opened; the product is then taken out, and the excess fabric or leather around the product is trimmed clean with electric scissors to obtain a finished polyurethane yoga mat.

[0112] Comparative Example 2

[0113] The difference between this comparative example and Example 1 is that the components of material A do not include heat-expandable microspheres.

[0114] Comparative Example 3

[0115] The difference between this comparative example and Example 1 is that the composition of material A does not include filling fiber.

[0116] Performance testing methods

[0117] The sound insulation performance of the yoga mat was tested using a four-microphone standing wave tube model 7758 produced by BRUEL&KJAER, Denmark. The test frequency was 80-1600Hz, the test temperature was 25°C room temperature, and the sample size was a circle with a diameter of 100mm, which was cut from the finished yoga mat. The average sound insulation within the test frequency range was recorded. Taking the average sound insulation corresponding to the sample of Comparative Example 1 as a benchmark, the ratio of the average sound insulation of each embodiment and comparative example to the average sound insulation of Comparative Example 1 was calculated, and the ratio was recorded as the relative sound insulation rate. The calculation result of the relative sound insulation rate was expressed as a percentage, as shown in Table 10.

[0118] Table 10 Relative sound insulation rate

[0119] sample Relative sound insulation rate / % sample Relative sound insulation rate / % Example 1 136.2 Embodiment 18 145.4 Example 2 137.2 Embodiment 19 145.6 Example 3 137.6 Embodiment 20 146.4 Example 4 137.8 Embodiment 21 147.5 Example 5 138.0 Embodiment 22 147.8 Example 6 140.1 Embodiment 23 148.1 Example 7 140.4 Embodiment 24 148.5 Example 8 140.7 Embodiment 25 149.0 Example 9 141.2 Embodiment 26 149.8 Example 10 141.5 Embodiment 27 150.4 Embodiment 11 141.8 Embodiment 28 151.9 Example 12 142.2 Embodiment 29 153.1 Embodiment 13 142.7 Embodiment 30 155.4 Embodiment 14 143.1 Embodiment 31 157.9 Embodiment 15 144.6 Comparative Example 1 100.0 Example 16 144.9 Comparative Example 2 107.5 Embodiment 17 145.1 Comparative Example 3 112.6

[0120] Combining Examples 1-5 and Comparative Example 1 and Table 10, it can be seen that the relative sound insulation rates measured in Examples 1-5 are higher than those in Comparative Example 1, indicating that the noise is more obviously attenuated after passing through the yoga mat samples of Examples 1-5. It can be seen that the yoga mat of the present application can not only effectively block the noise emitted by the user in actual use, but also effectively isolate the noise from the ground when the user lies on the yoga mat to rest, which is conducive to improving the rest quality of the user.

[0121] Combining Example 1 and Comparative Examples 2-3 and Table 10, it can be seen that when the heat-expandable microspheres and filling fibers are not added to the polyurethane formula system at the same time, the relative sound insulation rate of the yoga mat sample is low, indicating that the sound insulation effect of the yoga mat in these two cases is poor.

[0122] It can be seen from Example 5, Examples 6-10 and Table 10 that the use of bamboo fibers pretreated with sodium hydroxide can improve the sound insulation effect of the yoga mat. When the bamboo fibers are pretreated with a sodium hydroxide solution having a mass fraction of 15-22% sodium hydroxide, the sound insulation effect of the yoga mat is relatively good.

[0123] It can be seen from Examples 10-14 and Table 10 that the use of bamboo fibers soaked in a sodium hydroxide solution for 100-120 min is more helpful in improving the sound insulation effect of the yoga mat.

[0124] It can be seen from Example 14, Examples 15-19 and Table 10 that the sound insulation effect of the yoga mat can be improved by using both bamboo fiber and modified bamboo fiber as filling fiber.

[0125] It can be seen from Examples 19-23 and Table 10 that in the method for preparing modified bamboo fibers, when the pretreated bamboo fibers are added to the silane modification liquid at a ratio of 1 kg: (6-8) L, the silane modification liquid modifies the bamboo fibers more thoroughly, which helps to fully improve the sound insulation performance of the yoga mat.

[0126] It can be seen from Examples 23-27 and Table 10 that in the method for preparing modified bamboo fiber, when the amount of nano-mica powder is 12-17% of the weight of the pretreated bamboo fiber, it helps to fully improve the sound insulation performance of the yoga mat.

[0127] It can be seen from Examples 27-31 and Table 10 that in the method for preparing modified bamboo fiber, when the filling fiber is mixed with bamboo original fiber and modified bamboo fiber in a weight ratio of (1-3):1, it helps to fully overcome the defect that the filling fiber is easy to agglomerate, thereby improving the sound insulation performance of the yoga mat.

[0128] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A foldable yoga mat for nap, characterized in that: The yoga mat comprises a fabric and a polyurethane elastic layer, wherein the polyurethane elastic layer is prepared by mixing material A and material B in a weight ratio of (1.8-1.84):1; the material A comprises the following components in parts by weight: 90-98 parts of polyether polyol, 0.5-0.7 parts of antioxidant, 2-2.4 parts of deionized water, 0.4-0.6 parts of surfactant, 0.6-0.8 parts of catalyst, 4-10 parts of filling fiber, and 1.8-2.4 parts of thermal expansion microspheres; the filling fiber comprises bamboo fiber, and the components of the material B comprise diisocyanate and a pore opening agent; The filling fiber is formed by mixing bamboo fiber and modified bamboo fiber in a weight ratio of (1-5):1, and the modified bamboo fiber is prepared according to the following method: (1) mixing tetraethyl orthosilicate, hydroxymethyltriethoxysilane, deionized water and anhydrous ethanol in a molar ratio of 1:(0.6-1):(8-10):(30-34) to obtain a silane-modified liquid for later use; (2) adding the pretreated bamboo fibers and nano-mica powder to the silane modification solution to obtain a mixed solution, adjusting the pH of the mixed solution to 3-4, and ultrasonically dispersing the mixed solution in a constant temperature water bath at 45-50°C for 90-120 minutes, taking out the fibers from the mixed solution after standing for 3-4 hours, and drying them to obtain modified bamboo fibers; in this step, the pretreated bamboo fibers are added to the silane modification solution at a ratio of 1 kg: (6-8) L, and the amount of the nano-mica powder is 5-17% of the weight of the pretreated bamboo fibers; The bamboo fiber is pretreated before use according to the following method: A sodium hydroxide solution with a mass fraction of 22% is prepared for use; bamboo fibers are added to the sodium hydroxide solution and soaked for 120 minutes, and then the bamboo fibers are fished out and dried to complete the pretreatment of the bamboo fibers; in the method for pretreating the bamboo fibers, the mass fraction of sodium hydroxide in the sodium hydroxide solution is 15-22%.

2. The nap folding yoga mat according to claim 1, characterized in that: In the step (2) of preparing the modified bamboo fiber, the amount of nano-mica powder used is 12-17% of the weight of the pretreated bamboo fiber.

3. The nap folding yoga mat according to claim 1, characterized in that: The filling fiber is formed by mixing bamboo original fiber and modified bamboo fiber in a weight ratio of (1-3):

1.

4. The method for preparing a nap folding yoga mat according to any one of claims 1 to 3, characterized in that: The following steps are involved: (1) Mix polyether polyol, antioxidant, deionized water, surfactant, catalyst, filling fiber, and heat-expandable microspheres to obtain material A; mix diisocyanate and pore-opening agent to obtain material B; lay the fabric in a mold for later use; (2) Mix material A and material B, inject the obtained mixture into a mold, react at 40-50°C for 5-6 minutes, then pre-bake the obtained product at 80-90°C for 50-60 seconds, and then bake at 170-180°C for 40-60 seconds, and then cool, demold and cut to obtain a nap folding yoga mat.

Citation Information

Patent Citations

  • Novel hard aerogel foam and preparation method thereof

    CN111320842A

  • Impact-resistant automobile front wall sound insulation pad and preparation method thereof

    CN112625334A

  • Polyurethane yoga mat and preparation method thereof

    CN113956420A